PENGARUH WORK-LIFE BALANCE DAN EMPLOYEE WELL-BEING TERHADAP EMPLOYEE JOB SATISFACTION PADA PT. HERLINAH CIPTA PRATAMA (DODOL PICNIC) GARUT - Maharani, Kartika Tri; Nurhasan, Rohimat; Rawati Suganda, Fitrin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to examine the effect of work-life balance and employee well-being on employee job satisfaction at PT. Herlinah Cipta Pratama (Dodol Picnic) Garut. The study uses a quantitative design that is descriptive in nature to illustrate the data empirically, and associative to assess the statistical connections between variables. Data collection was carried out through the division of questionnaires with a five-point Likert scale involving 100 respondents determined through a purposive sampling approach, with the consideration that they met the characteristics that suit the needs of the study. The data was analyzed using the Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS-SEM) with the help of SmartPLS software. The observation results show that work-life balance and employee well-being have a positive and significant impact on employee job satisfaction. Employee well-being makes a slightly greater contribution than work-life balance to shaping employee job satisfaction. These results suggest that companies that support work-life balance and employee well-being generally experience higher levels of job satisfaction and motivation among their employees.